The War on Sex - Halperin, David M.; Hoppe, Trevor (Duke University Press, 2017)
Frontmatter -- Contents -- Foreword: Thinking Sex and Justice -- Introduction: The War on Sex -- 1. The New Pariahs: -- 2. Sympathy for the Devil: -- 3. Queer Disavowal: -- 4. A New Iron Closet -- 6. Sex Panic, Psychiatry, and the Expansion of the Carceral State -- 7. The Creation of the Modern Sex Offender -- 8. For What They Might Do: -- 9. The “Hooker Teacher” Tells All -- 10. Carceral Politics as Gender Justice? -- 11. California’s Proposition 35 and the Trouble with Trafficking -- 12. HIV: Prosecution or Prevention? -- 14. HIV Care as Social Rehabilitation -- 15. The New War on Sex -- 16. Building a Movement for Justice: -- 17. Bringing Sex to the Table of Justice -- Afterword: How You Can Get Involved -- Contributors -- Index